INFLUENCING URBAN COMMERCIAL DEVELOPMENTS: PERSPECTIVES FROM EXTERNALITY THEORY - Carter, John (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
The development and construction of urban commercial complexes wield a profound influence on urban ontology and equilibrium. These complexes transcend mere architectural spaces; they represent a distinctive amalgamation of citywide public and social resources. Instead of being solely driven by profit, these complexes ought to prioritize the societal worth of their offerings. Recognizing the externalities associated with commercial complexes and reconfiguring the symbiotic relationship between internal and external value interests within the urban system's various components can usher in mutual growth with the city and contribute to its ongoing evolution.